A sustainable mouse karyotype created by programmed chromosome fusion - Wang, Li-Bin; Li, Zhi-Kun; Wang, Le-Yun; Xu, Kai; Ji, Tian-Tian; Mao, Yi-Huan; Ma, Si-Nan; Liu, Tao; Tu, Cheng-Fang; Zhao, Qian; Fan, Xu-Ning; Liu, Chao; et al. (Science (American Association for the Advancement of Science), 2022)
Chromosome engineering has been attempted successfully in yeast but remains challenging in higher eukaryotes, including mammals. Here, we report programmed chromosome ligation in mice that resulted in the creation of new karyotypes in the lab. Using haploid embryonic stem cells and gene editing, we fused the two largest mouse chromosomes, chromosomes 1 and 2, and two medium-size chromosomes, chromosomes 4 and 5. Chromatin conformation and stem cell differentiation were minimally affected. However, karyotypes carrying fused chromosomes 1 and 2 resulted in arrested mitosis, polyploidization, and embryonic lethality, whereas a smaller fused chromosome composed of chromosomes 4 and 5 was able to be passed on to homozygous offspring. Our results suggest the feasibility of chromosome-level engineering in mammals. One of the goals in synthetic biology is to generate complex multicellular life with designed DNA sequences. Being able to manipulate DNA at large scales, including at the chromosome level, is an important step toward this goal. So far, chromosome-level genetic engineering has been accomplished only in haploid yeast. By applying gene editing to haploid embryonic stem cells, Wang et al . achieved whole-chromosome ligations in mice, and successfully derived animals with 19 pairs of chromosomes, one pair fewer than is standard in this species. —DJ The ability to perform karyotype engineering in laboratory mice has been developed using haploid stem cells and gene editing.